Status and Challenges of Plant-Anticancer Compounds in Cancer Treatment - Paula Garcia-Oliveira; Paz Otero; Antia Gonzalez Pereira; Franklin Chamorro; Maria Carpena; Javier Echave; Maria Fraga-Corral; Jesus Simal-Gandara; Miguel Angel Prieto (MDPI AG, 2021)
Nowadays, cancer is one of the deadliest diseases in the world, which has been estimated to cause 9.9 million deaths in 2020. Conventional treatments for cancer commonly involve mono-chemotherapy or a combination of radiotherapy and mono-chemotherapy. However, the negative side effects of these approaches have been extensively reported and have prompted the search of new therapeutic drugs. In this context, scientific community started to look for innovative sources of anticancer compounds in natural sources, including traditional plants. Currently, numerous studies have evaluated the anticancer properties of natural compounds derived from plants, both in vitro and in vivo. In pre-clinical stages, some promising compounds could be mentioned, such as the sulforaphane or different phenolic compounds. On the other hand, some phytochemicals obtained positive results in clinical stages and were further approved for cancer treatment, such as vinca alkaloids or the paclitaxel. Nevertheless, these compounds are not exempt of limitations, such as low solubility, restricted effect on their own, negative side-effects, etc. This review aims to compile the information about the current phytochemicals used for cancer treatment and also promising candidates, main action mechanisms and also reported limitations. In this sense, some strategies to face the limitations have been considered, such as nano-based formulations to improve solubility or chemical modification to reduce toxicity. In conclusion, although more research is still necessary to develop more efficient and safe phytochemical drugs, more of these compounds might be used in future cancer therapies.